Combined effect of Cefixime and Azithromycin against multiple antibiotics resistant Klebsiella pneumoniae and Pseudomonas aeruginosa - Salahuddin, Fariba (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.